Transition‐Metal‐Free Synthesis of Biarylmethanes from Aryl Iodides and Benzylic Ketones. Issue 66 (31st October 2018) - Pichette Drapeau, Martin; Tlili, Anis; Zaid, Yassir; Toummini, Dounia; Ouazzani Chahdi, Fouad; Sotiropoulos, Jean‐Marc; Ollevier, Thierry; Taillefer, Marc
Abstract: An original metal‐free procedure for the synthesis of biarylmethanes is disclosed herein. The reactions occur with high selectivity starting from aryl iodides and benzylic ketones in the presence of superbasic media (CsOH/DMSO). This procedure allows a straightforward access to a wide range of biarylmethane derivatives substituted with electron‐withdrawing and ‐donating substituents. Abstract : Superbase for C−C coupling : The synthesis of biarylmethane derivatives is performed herein under transition‐metal‐free conditions starting from a wide range of aryl iodides and benzylic ketones. The key to success is the employment of the "superbase" (CsOH/DMSO). The desired products are obtained in very good yield and selectivity.